2014
DOI: 10.1637/10706-102413.1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics of Chinese Precocious Strain ofEimeria acervulinaand Its Immune Efficacy Against Different Field Strains

Abstract: In this study, the biologic characteristics of one experimental precocious strain of Eimeria acervulina and seven field isolates from different geographic locations in China were compared, and the immune efficacy of two precocious strains against coccidiosis in chickens was assessed to explore their potential use as coccidiosis vaccines. All the different strains were purified by single oocyst separation and their monospecificity was confirmed using E acervulina-specific PCR assays. The average sizes of E. ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similarly, just four nucleotide polymorphisms exist between EmAMA-1 coding sequences from the E. maxima Houghton and Weybridge laboratory strains, two causing non-synonymous changes, one situated in the putative pro-domain and one located in domain 1 [9,66]. Nonetheless, despite such limited diversity within the coding region of at least one vaccine candidate, strain specific immune escape has been reported in vivo for E. acervulina [67,68], E. mitis [69], E. maxima [70] and E.…”
Section: The Relevance Of Antigenic Diversitymentioning
confidence: 99%
“…Similarly, just four nucleotide polymorphisms exist between EmAMA-1 coding sequences from the E. maxima Houghton and Weybridge laboratory strains, two causing non-synonymous changes, one situated in the putative pro-domain and one located in domain 1 [9,66]. Nonetheless, despite such limited diversity within the coding region of at least one vaccine candidate, strain specific immune escape has been reported in vivo for E. acervulina [67,68], E. mitis [69], E. maxima [70] and E.…”
Section: The Relevance Of Antigenic Diversitymentioning
confidence: 99%
“…As against the background of allelic polymorphism among AMA-1 which has limited their use in P. falciparum, AMA-1 is a potential candidate for E. tenella vaccine due to its inhibitory capacity on parasite invasion (Jiang et al 2012). Although low level of allelic polymorphism has been reported among AMA-1 of E. tenella and E. maxima, in vivo studies have also shown some degree of strainspecific immune escape (resistance) among the vaccine candidate for E. tenella, E. acervulina and E. maxima (Awad et al 2013;Healer et al 2004;Smith et al 2002;Wu et al 2014). Therefore, allelic diversity in this candidate vaccine antigen is a potential constraint to the effectiveness of subunit vaccine use against coccidiosis in poultry.…”
Section: Control Measure Of Coccidiosismentioning
confidence: 99%